The use of proper and improper interjections by students of Spanish as a foreign language: frequencies of use and values reflected in the CAES corpus - Sánchez Morillas, Carmen María; Valero Fernández, Pilar (Didáctica. Lengua y Literatura, 2022)
Within the communicative methodology of teaching foreign languages or second languages, a special emphasis has been placed on the teaching of different linguistic components from the analytical perspective of the student's language level. However, within the grammatical level, it is an undeniable fact that there are particles, in this case interjections, that are still relegated to oblivion in Spanish manuals or other teaching materials. For this reason, this research will be focused on demonstrating the use that students of Spanish as a Foreign Language make of them according to their level of language (from level A1 to level C1, according to the CEFR), as well as showing the inventory of primary and secondary interjections that they know and use in their written texts, the frequency of use, the function they have and, finally, the particularities they present. To carry out this research, both quantitative and qualitative, it will be used the latest version (1.3., April 2020) of the data extracted from the Corpus of Learners of Spanish as a Foreign Language (CAES), prepared by the University of Santiago de Compostela from the written productions of foreign students of different linguistic levels and six different mother tongues: Arabic, Mandarin Chinese, French, English, Portuguese and Russian.
Keywords: interjection; Spanish as a foreign language; CAES corpus